Microbial phosphate solubilization mechanisms in P solubilizing in andisol - Marpaung, Agustina Erlinda; Sabrina, Tengku; Rauf, Abdul; Susilowati, Dwi Ningsih; Siregar, Luthfi Aziz Mahmud (Kultivasi, 2024)
Phosphate (P) nutrient plays a significant role in plant growth and yield. P is an essential element that plays an important role in photosynthesis and root development. Phosphate nutrient availability is deficient in some soil types due to retention, such as in Andisol soil types. High phosphate retention in Andisol soil types causes P nutrients to be unavailable to plants and can reduce crop yields. The availability of P in Andisol soils can be done, among others, by applying phosphate solubilizing microbes. Phosphate solubilizing microorganisms are soil microorganisms consisting of bacteria and fungi that can mineralize organic P, dissolve inorganic P minerals, and store large amounts of P to make it available to plants. This literature review aims to determine the mechanism of phosphate-solubilizing microbes in P dissolution in Andisol soil. The methods used in this systematic review are collecting data through the internet and utilizing recognized sources such as Science Direct, Research Gate, Google Scholar, and Web of Science. Content analysis was performed on the collected data, and the results were organized into thematic categories. Furthermore, the findings are presented descriptively with the help of tables to facilitate understanding. Since phosphate-solubilizing microorganisms can dissolve P in the soil through chemical and biological mechanisms, it can be concluded that phosphate-solubilizing microorganisms also have an important role in the soil P cycle. The implications of this literature review are to understand the retention of P nutrients in Andisols and how the dissolution mechanism works, as well as the use of microbes as a solution to increase phosphate dissolution so that it is available to plants.